Acute effects of wheel running on adult hippocampal precursor cells in mice are not caused by changes in cell cycle length or S phase length - Fischer, Tim J.; Walker, Tara L.; Overall, Rupert W.; Brandt, Moritz D.; Kempermann, Gerd (Frontiers in Neuroscience, 2014)
Exercise stimulates cellular brain plasticity by extending the pool of proliferating neural precursor cells in the adult hippocampus. This effect has been investigated extensively, but the most immediate cellular effect induced by exercise that results in this acute increase in the number of cycling cells remained unclear. In the developing brain as well as adult pathological models, cell cycle alterations have a major influence on the balance between proliferative and neurogenic divisions. In this study we investigated whether this might also apply to the acute physiological pro-neurogenic stimulus of physical exercise in adulthood. Do changes in cell cycle precede the measurable increase in proliferation? After 5 days of voluntary wheel running, however, we measured only a very small, statistically not significant acceleration in cell cycle, which could not quantitatively explain the observed increase in proliferating cells after exercise. Thus, at this acute stage, changes at the level of cell cycle control is not the primary causal mechanism for the expansion of the precursor cell population, although with time after the stimulus changes in cell cycle of the entire population of labeled cells might be the result of the expanded pool of cells that have progressed to the advanced neurogenic stages with shorter cell cycle length.